Colored Rain on the West Coastal Region of India: Was it Due to a Dust Storm? - M. Satyanarayana ; S. Veerabuthiran ; D. Ramakrishna Rao ; B. Presennakumar (Aerosol Science and Technology, 38:24-26, 2004, 2004)
On 25 July 2001 some parts of Kerala in India on the west coast experienced the interesting phenomena called "colored rain." Atmospheric dust particles had been detected on the previous day using a multiwavelength lidar system located at nearby Trivandrum (8.33.N, 77.E) on the west coast of India. This study concludes that the dust generated from desert areas of the west Asian countries was also one of the sources of the observed colored rain.